The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1063/1.3545967
|View full text |Cite
|
Sign up to set email alerts
|

Two features at the two-dimensional freezing transitions

Abstract: We studied the two-dimensional freezing transitions in monolayers of microgel colloidal spheres with shortranged repulsions in video-microscopy experiments, and monolayers of hard disks, and Yukawa particles in simulations. These systems share two common features at the freezing points: (1) the bimodal distribution profile of the local orientational order parameter; (2) the two-body excess entropy, s 2 , reaches −4.5 ± 0.5 k B . Both features are robust and sensitive to the freezing points, so that they can po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Around φ = 0.65-0.69, however, there is a marked change in slope, which coincides with the start of the liquid-hexatic coexistence region. In [42] it was reported that at the melting transition −S 2 /k B takes the value of 4.5, which is indicated by the dashed horizontal line in figure 4(b). Our data reach this value at an area fraction of just over φ = 0.69, i.e.…”
Section: Excess Configurational Entropymentioning
confidence: 83%
“…Around φ = 0.65-0.69, however, there is a marked change in slope, which coincides with the start of the liquid-hexatic coexistence region. In [42] it was reported that at the melting transition −S 2 /k B takes the value of 4.5, which is indicated by the dashed horizontal line in figure 4(b). Our data reach this value at an area fraction of just over φ = 0.69, i.e.…”
Section: Excess Configurational Entropymentioning
confidence: 83%
“…However, the first-order nature of the liquid-hexatic transition is very weak, and the transition roughly obeys the KTHNY scenario. This basic behavior is common to other systems including particles interacting with soft repulsive potentials [13][14][15][16] and those with attractive potentials such as the Lennard-Jones potential [17], although it has recently be shown that the nature of the transitions depends on the softness of the potential in a delicate manner [16]. Monolayer granular matter has provided a model experimental system to study this fundamental problem.…”
Section: Introductionmentioning
confidence: 92%
“…The fluid becomes unstable when the average centre-to-centre distance between alternating nearest neighbors becomes shorter than two disk diameters and the resulting gap between them is shorter than hard-core diameter and does not allow for the central disk to wander. Such a caging concept allows for both the quantitative and qualitative description of the thermodynamics of freezing transition in monodisperse hard-disk fluid and has been already utilized to discuss percolation [8].…”
Section: Introductionmentioning
confidence: 99%